Overstretching Double-Stranded RNA, Double-Stranded DNA, and RNA-DNA Duplexes - Melkonyan, Lena (Biophys J, 2019)
Using single-molecule force measurements, we compare the overstretching transition of the four types of duplexes composed of DNA or RNA strands. Three of the four extremities of each double helix are attached to two microscopic beads, and a stretching force is applied with a dual-beam optical trapping interferometer. We find that overstretching occurs for all four duplexes with small differences between the plateau forces. Double-stranded RNA (dsRNA) exhibits a smooth transition in contrast to the other three duplexes that show sawtooth patterns, the latter being a characteristic signature of peeling. This difference is observed for a wide range of experimental conditions. We present a theoretical description that explains the difference and predicts that peeling and bubble formation do not occur in overstretching double-stranded RNA. Formation of S-RNA is proposed, an overstretching mechanism that contrary to the other two does not generate single strands. We suggest that this singular RNA property helps RNA structures to assemble and play their essential roles in the biological cell.